Eliminacion de virus y propagacion de clones en la yuca (Manihot esculenta Crantz) - Roca, W.; Nolt, Barry L.; Mafla, G.; Roa E, Julio César; Reyes, R. (International Center for Tropical Agriculture, 1991)
Several techniques used to eliminate viruses from cassava are described, namely heat therapy, apical tissue culture, and micropropagation. Virological tests to index cassava viruses are also indicated as follows: ELISA, dsRNA, mechanical inoculation of leaf sap in plants on Chenopodium quinoa, and grafting trials. Clones submitted to pathogenic tests can be maintained in vitro, avoiding the recontamination with pathogenic organisms. The interrelations existing between the different forms of in vitro conservation of cassava germplasm and the elimination of diseases, micropropagation, distribution, and traditional conservation through seed and field plantations (basic vs. active collections) are indicated. The use of in vitro clonal propagation in cassava and the combination of different techniques to satisfy all multiplication needs are discussed, namely micropropagation through single-node cultures, multiple shoot culture, and somatic embryogenesis. Several examples are given that illustrate that rehabilitation of regional cassava cv. is a strategy to produce cassava in the poorer regions of the tropics in the short term. (CIAT)